An Introduction to Marie-Louise von Franz's Number and Time. (2nd October 2018) - Sparks, J. Gary
Abstract : Number and Time: Reflections Leading toward the Unification of Depth Psychology and Physics, by Marie-Louise von Franz (1974 ), explores parallels between the understanding of psychological healing in Jungian psychology and the theory of subatomic particles in quantum physics. Von Franz compares number symbolism in dreams with the mathematical structure of matter to link these two realms of life. The parallel role of numbers in the psyche and in matter is described to explain the interrelationship of our inner images and the outer world, as well to represent fundamental processes of personal development.